The growth of private higher education in Brazil: implications for issues of equity, quality and public benefit - McCowan, Tristan (Education Policy Analysis Archives, 2005)
There has been a dramatic growth in private higher education in Brazil in recent years. The World Bank has promoted this expansion on the basis of the private providers" ability to ensure a rapid increase in enrolment, to improve quality through competition between institutions, and to secure benefits for society at little public cost. However, the charging of fees means that the majority of Brazilians do not have access, and that inequalities are reproduced due to the relation between course costs and the value of the final diploma. Equitable access is, therefore, far from being achieved and is unlikely even with an increase in student loans and government subsidies. The contribution of private universities to the long-term development of society is seen to be limited due to lack of investment in research and community service.